A Brief History of Chinese Design Thought - Shao, Qi. author. aut Link
IX, 276 p. 174 illus., 158 illus. in color.
Keywords: This book introduces readers to the history of design thinking in pre-modern China. The content is structured according to successive dynasties, covering the seven major periods of the pre-Qin, Qin and Han, Wei and Jin, Sui and Tang, Song and Yuan, Ming, and Qing dynasties. Each chapter introduces the most representative individuals of the period and discusses their work and ideas in order to reveal the national and cultural features of the respective periods. A distinctive feature of cultural identity running through the long course of China’s historical development is the argument that actions are determined by ideas: Such a view can be found in long-standing thinking on art, design, and creativity. The book demonstrates that conscious design is the vital link between the ideas that constitute human cultures and the physical objects that make up their resulting material cultures. It is the attribute of design that defines what it is to be human and also produces the physical evidence of the evolution of Chinese civilization. The book reveals the integrated characteristics of Chinese culture and art and shows how both changing and recurring ideologies have influenced Chinese design practice since the ancient Shang and Zhou dynasties and how these forces have shaped the spirit and materiality of Chinese civilization. Design is the cornerstone that has made China one of the major contributors to human civilization throughout the thousands of years of its history. Given its focus, the book largely appeals to two main audiences: an academic readership of students and researchers interested in cultural studies and, a more general one, consisting of those interested in international comparisons and wishing to learn more about Chinese history, society, and culture. In order to appeal to both, the book is written in a clear and accessible language.